A Review of the Psychometric Properties of the Child and Adolescent Needs and Strengths (CANS): Perspectives on the Present State of the Literature and Future Directions. Issue 3 (3rd July 2022) - Brown, Cameron C.; Wang, Eugene W.; Goad, Chloe
ABSTRACT: The Child and Adolescent Needs and Strengths (CANS) is a comprehensive tool assessing functioning, strengths, acculturation, caregiver needs/resources, behavioral/emotional needs, and risk behaviors of youth and children. Although this tool is widely used within the United States, minimal work has been published overviewing the tool, synthesizing existing research that utilizes it, and highlighting studies that specifically examine its psychometric properties such as reliability and validity. The purpose of this article is to overview much of the existing research and literature that has been published in peer-reviewed journals that employs the CANS to offer researchers, helping professionals, families, agencies, and institutions a synopsis of the current status of the tool. Additionally, suggestions and future directions of the CANS are offered with the intent of strengthening and solidifying the tool's understanding, utility, and application.